Let p(x) = 30 x^3 -7 x^2 - 7 x + 2. Prove that (2x + 1) is a factor of p(x) and factorise p(x) completely.

Using the Factor Theorem, we know that (2x + 1) = 2(x + 1/2) = 2(x - (-1/2) ) is a factor of p(x) if and only if p(-1/2) = 0, which is true. Now that we know a factor of p(x), we use the polynomial division method to find p(x) = (2x + 1)(15 x^2 - 11x + 2) and factorise the quadratic with some simple algebra 15 x^2 - 11x + 2 = 15 x^2 - 5x - 6x + 2 = 5x(3x - 1) - 2(3x - 1) = (3x - 1)(5x - 2), which gives us the final answer: p(x) = (2x + 1)(3x - 1)(5x - 2).

Related Maths A Level answers

All answers ▸

How do you solve the equation e^2x - 2e^x - 3 = 0 ?


express the following fraction in the form of m + (n)^1/2. the fraction is ((3*(5)^1/2)^2 - 7)/(3 + 7*(5)^1/2). where m,n are real numbers.


Using implicit differentiation, write the expression "3y^2 = 4x^3 + x" in terms of "dy/dx"


Given the function f(x) = (x^2)sin(x), find f'(x).


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences